Effectiveness of interventions to improve patient handover in surgery: a systematic review - Pucher,PH; Johnston,MJ; Aggarwal,R; Arora,S; Darzi,A (Surgery, 2015)
Background:Handover of patient care is a critical process in the transfer of information between clinical teams and clinicians during transitions in patient care. The handover process may take many forms and is often unstructured and unstandardized, potentially resulting in error and the potential for patient harm. The Joint Commission has implicated such errors in up to 80% of sentinel events and has published guidelines (using an acronym termed SHARE) for the development of intervention tools for handover. This study aims to review interventions to improve handovers in surgery and to assess compliance of described methodologies with the guidelines of the Joint Commission for design and implementation of handover improvement tools.Methods:A systematic review was conducted in line with MOOSE guidelines. Electronic databases Medline, EMBASE, and PsyInfo were searched and interventions to improve surgical handover identified. Intervention types, development methods, and outcomes were compared between studies and assessed against SHARE criteria.Results:Nineteen studies were included. These studies included paper and computerized checklists, proformas, and/or standardized operating protocols for handover. All reported some degree of improvement in handover. Description of development methods, staff training, and follow-up outcome data was poor. Only a single study was able to demonstrate compliance with all 5 domains guidelines of the of Joint Commission.Conclusion:Improvements in information transfer may be achieved through checklist- or proforma-based interventions in surgical handover. Although initial data appear promising, future research must be backed by robust study design, relevant outcomes, and clinical implementation strategies to identify the most effective means to improve information transfer and optimize patient outcomes.